Identification of madangamine A as a novel lysosomotropic agent to inhibit autophagy. (15th March 2021) - Miura, Kazuki; Kawano, Sayaka; Suto, Takahiro; Sato, Takaaki; Chida, Noritaka; Simizu, Siro
Graphical abstract: Highlights: Madangamine A acts as a lysosomotropic agent in cells. Madangamine A is a novel autophagy inhibitor. Inhibition of lysosome function is responsible for anti-proliferative activity of madangamine A. Abstract: Madangamines are marine natural products isolated from Xestospongia ingens, and madangamine A–E with a different D-ring structure have been reported. We have reported that madangamine A has strong anti-proliferative activity against various human cancer cell lines. In this study, to clarify the anti-proliferative activity of madangamine A, we searched for molecular target of the madangamine A in human cells. Treatment with madangamine A increased the levels of LC3-II and p62, autophagy-related proteins, concomitant with growth inhibition. Moreover, madangamine A resulted in lysosome enlargement and increase in lysosomal pH, which are same phenomena observed in chloroquine-treated cells. These results suggest that madangamine A is a novel lysosome inhibitor, and the anti-proliferative activity of madangamine A is due to the inhibition of lysosome function.